Ustad Qasim's Preaching Strategy Based on Local Wisdom in the Meratus Hinterland: Challenges and Solutions / Strategi Dakwah Islam Berbasis Kearifan Lokal di Pedalaman Meratus: Tantangan dan Solusi - Fadil, Muhammad Ikhsan; Hudaya, Hairul; Nor, Asikin (Alhadharah: Jurnal Ilmu Dakwah, 2024)
Preaching in rural communities has its own challenges, including the harsh character of the community, limited facilities, and diversity of beliefs. Effective approaches and strategies are needed in dealing with these conditions. This study aims to explore the problems and strategies of local wisdom-based da'wah applied by Ustad Qasim in the Meratus Inland, Hulu Sungai Tengah Regency. This research uses qualitative methods with data collection techniques through in-depth interviews, participatory observation, and document analysis. The results showed several problems faced, namely: 1) the location that is difficult to reach, 2) the hard and diverse character of the community, 3) limited facilities, 4) diversity of beliefs (Islam, Christianity, and Kaharingan), and 5) the lack of public understanding of the teachings of Islam. The da'wah strategies applied include: 1) optimizing the function of the mosque and the role of the community, 2) communication and adaptation strategies, 3) educational and exemplary strategies, and 4) economic development for students. This research contributes to the development of local culture-based contextual da'wah methods with a holistic da'wah model that integrates religious education, economic empowerment, and social cohesion. Through this strategy, Ustad Qasim succeeded in overcoming the challenges of da'wah in the Meratus Hinterland, creating positive changes, and strengthening community social harmony.